The U.S. Constitution - Teitelbaum, Michael (Chanhassen, Minn. : Child's World, 2005)
Presents a history of the document that provides the framework for the government of the United States, from the Preamble to the Amendments; includes a timeline and interesting fact sidebars.
Before the Constitution -- Creating the Constitution -- The foundation: preamble and articles -- A living document: the amendments.
"Spirit of America."
Includes bibliographical references and index.
Keywords: Constitutional law -- United States -- Juvenile literature